Proyecto de diseño e implementación de un documental sobre tribus urbanas en la ciudad de Guayaquil - Chedraui Aguirre, Lorraine Tonika (2010)
In our city different youthful communities also denominated urban tribes exist, formed for diverse reasons between which we can indicate the necessity to belong to a group. These communities are formed in their majority of young people within the thirteen to thirty and five years old, that share a taste by some activity or especially feel affinity towards a type of music. They have its beginnings in the middle of the Sixties, mainly influenced by the United States where many of these movements were originated. Over the years the existence of more communities in our society due to social factors and innovations within music and technology has been increased. There is a big ignorance about these groupings causing prejudices and stereotypes about them, that is why it is necesary that de public take consciousness about this social phenomenon and look for know more about it, this is the fundamental reason to make this Project. Our purpose is to present, through the opinion and knouledge of specialists and members of the urban tribes, about how they really are and in that way clarify missed concepts on these groups.